High-value minerals and resource bargaining in a time of crisis: A case study on the diamond fields of Marange, Zimbabwe - Richard Saunders (United Nations Research Institute for Social Development (UNRISD), 2018)
In 2006, the discovery of world-class deposits of alluvial diamonds in Marange District in eastern Zimbabwe offered important opportunities for the mobilization of significant revenues in a period of severe and worsening economic and social crisis. The new resources quickly became the subject of intense contestation involving the state and a variety of actors including mining communities, civil society, the diamond industry and donors. The paper traces the evolution of these contestations over the course of three successive phases of alluvial exploitation. For each period, the study explores the key dynamics shaping the management of diamond production and trading, and assesses their impact on state-society relations and development outcomes. Particular focus falls on the implications of state capture for the state's institutional capacity and coherence, and the constraints on civil society's and donors' influence with state and business actors. The paper's findings underscore the limits of civil society and donor influence with government in strengthening resource governance through contestation over the management of high-value minerals. In a period of heightened political conflict, economic crisis and elite predation, social claims on resource mobilization were confronted by elite resistance. This resulted in attempts by the state to undermine the achievement and implementation of a workable social consensus around the management of diamond wealth. At the same time, various international legal and regulatory mechanisms established to strengthen resource governance proved to be severely limited in their ability to elicit greater transparency and accountability by both government and diamond miners.
Additional information: Prepared for the UNRISD project on Politics of Domestic Resource Mobilization for Social Development
Keywords: 330